Comparison of a fludarabine and melphalan combination‐based reduced toxicity conditioning with myeloablative conditioning by radiation and/or busulfan in acute myeloid leukemia in Japanese children and adolescents. Issue 5 (24th December 2014) - Ishida, Hiroyuki; Adachi, Souichi; Hasegawa, Daiichiro; Okamoto, Yasuhiro; Goto, Hiroaki; Inagaki, Jiro; Inoue, Masami; Koh, Katsuyoshi; Yabe, Hiromasa; Kawa, Keisei; Kato, Koji; Atsuta, Yoshiko; et al.
Abstract : Background: The relative efficacy of allogeneic hematopoietic cell transplantation (allo‐HCT) after reduced toxicity conditioning (RTC) compared with standard myeloablative conditioning (MAC) in pediatric patients with acute myeloid leukemia (AML) has not been studied extensively. To address whether RTC is a feasible approach for pediatric patients with AML in remission, we performed a retrospective investigation of the outcomes of the first transplant in patients who had received an allo‐HCT after RTC or standard MAC, using nationwide registration data collected between 2000 and 2011 in Japan. Procedure: We compared a fludarabine (Flu) and melphalan (Mel)‐based regimen (RTC; n = 34) with total body irradiation (TBI) and/or busulfan (Bu)‐based conditioning (MAC; n = 102) in demographic‐ and disease‐criteria‐matched childhood and adolescent patients with AML in first or second complete remission (CR1/CR2). Results: The incidence of engraftment, early complications, grade II–IV acute graft‐versus‐host disease (GVHD), and chronic GVHD were similar in each conditioning group. The risk of relapse (25% vs . 26%) and non‐relapse mortality (13% vs . 11%) after 3 years did not differ between these groups, and univariate and multivariate analyses demonstrated that the 3‐year overall survival (OS) rates after Flu/Mel‐RTC and MAC were comparable (mean, 72% [range, 51–85%] and 68% [range, 58–77%], respectively). Conclusions: The results suggest that the Flu/Mel‐RTC regimen is a clinically acceptable conditioning strategy for childhood and adolescent patients with AML in remission. Although this retrospective, registry‐based analysis has several limitations, RTC deserves to be further investigated in prospective trials. Pediatr Blood Cancer 2015;62:883–889. © 2014 Wiley Periodicals, Inc.